Theoretical study of elliptic drum of vertical spindle cotton picker - Ravutov, Shavkat; Rakhimov, Abdumalik; Ibragimov, Gafurjan (IIUM Faculty of Engineering, 2025)
The article focuses on the structural optimization of the planetary mechanism of the spindle drum of a vertical-spindle cotton-picking machine in Uzbekistan and discusses the problems of synthesizing a new vertical-spindle drum that significantly enhances the efficiency of using spindles and increases the productivity of the machine. Utilizing the interaction characteristics of drum spindles with cotton plants and ensuring the effective functioning of spindle friction drives, it is theoretically justified that the trajectory of spindle relative motion has an elliptical shape. Special attention is given to the shape and dimensions of the directional path, ensuring the elliptical movement of the spindles. An analytical expression is obtained, and a convenient calculation algorithm is developed to automate the investigation of the influence of the dimensions of drum mechanism parts onthe directional path shape and its dimensions. The theoretical results allow for preliminary conclusions regarding the dynamic processes occurring during drum operation and provide recommendations for selecting the directional path shape and dimensions.